Genetic divergence and adaptation of an isolated European lobster population in the Netherlands - Ellis, Charlie D; Paris, Josephine R; Jenkins, Tom L; van Stralen, Marnix R; Steins, Nathalie A; Schotanus, Jildou; Stevens, Jamie R (ICES journal of marine science, 2024)
Identifying isolated populations is a key step towards enacting effective conservation management. European lobsters (Homarus gammarus) from Oosterschelde in the Netherlands are subject to fishery pressure and have previously been reported as genetically differentiated. They are also putatively of transplanted origin and have subsequently endured recent bottlenecking and environmental change. We assessed Oosterschelde lobsters to evaluate their demographic independence and appraise potential founder effects and evolutionary responses to isolation. Using restriction-site associated DNA sequencing, we genotyped 6185 single nucleotide polymorphisms across 188 individuals from 27 sites across the Atlantic range of H. gammarus to investigate population genetic diversity, structure, and potential adaptation. Our results show that Oosterschelde lobsters are genetically divergent from other stocks. We evidence extensive differentiation via both neutral and outlier loci, indicative of strong biophysical and demographic isolation, and detect signatures of reduced genetic diversity that may reflect weak founder effects or subsequent population contractions. Among outlier loci, we identify candidates for range-wide local adaptation via variants in genes of important biological functionality and link a private allele of Oosterschelde to a locus potentially conveying adaptive tolerance to environmental hypoxia. Given our findings, we advise proactive monitoring of Oosterschelde lobsters to explore whether existing management measures effectively conserve this discrete, self-recruiting population.